Using the WSPR Mode for Antenna Performance Evaluation and Propagation Assessment on the 160-m Band - Jurgen Vanhamel; Walter Machiels; Hervé Lamy (International Journal of Antennas and Propagation)
In the last couple of years, the use of weak signal propagation reporter (WSPR) has grown significantly in the radio amateur community and beyond. This protocol allows to probe potential propagation paths between radio transceivers, operating at a low-power level. The protocol decodes the received signals and translates them into appropriate signal-to-noise ratio levels, which reveal the possible propagation paths between the transmitter and receiver using ionospheric reflections. In this article, specifically the 160-m radio amateur band is addressed. This band used less intensity for WSPR communication, compared to the other radio amateur bands (80 m and 40 m). Additionally, the 160-m band has specific features such as the link between propagation performance and the Earth’s electron gyro-effect. The aim of this article is to address these features experimentally. First, two identical 160-m band WSPR receiver stations are conditioned to compare the performance of different 160-m band antennas. Each setup, separated by a limited distance, generates almost identical SNR reports, allowing the comparison between the two antennas. Second, a more extended experimental investigation of the propagation path performance on the 160-m band reveals information on the radio wave behaviour between the transmitter and receiver. The first experiment allowed the identification of the most optimal antenna, specifically in the 160-m band. The second experiment shows that the SNR values can vary depending on the polarization shift of the received signal. Possibly, this can be linked to the effect of the magnetic field of the Earth via the electron gyro-frequency.